2011
DOI: 10.3315/jdcr.2010.1056
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous frame shift mutation in ECM1 gene in two siblings with lipoid proteinosis

Abstract: Background: The extracellular matrix protein 1 (ECM1) is a glycoprotein, expressed in skin and other tissues. Loss-of-function mutation in ECM1 causes a rare autosomal recessive disorder called lipoid proteinosis. Lipoid proteinosis is presented by varying degrees of skin scars, beaded papules along the eyelid margins, variable signs of hoarseness of voice and respiratory disorders. More than 250 cases of this disorder have been described in the literature, but occurrence of lipoid proteinosis in siblings is v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Agarose gel electrophoresis was performed using standard procedure; 5 µl PCR products were mixed with 1 µl loading buffer (6X) and loaded into 0.8% agarose gel. The electrophoresis was performed in a 120 V electrical field for 10 min as previously described (19).…”
Section: Methodsmentioning
confidence: 99%
“…Agarose gel electrophoresis was performed using standard procedure; 5 µl PCR products were mixed with 1 µl loading buffer (6X) and loaded into 0.8% agarose gel. The electrophoresis was performed in a 120 V electrical field for 10 min as previously described (19).…”
Section: Methodsmentioning
confidence: 99%
“…No definitive age, sex or race predilections exist. There is a documented autosomal recessive inheritance as there is usually a history of consanguinity among the unaffected parents [9]. A mental sub normality is seen only when it is transmitted by autosomal dominant inheritance due to the mutant genes [3].…”
Section: Case Reportmentioning
confidence: 99%
“…A number of recent genetic studies reported the involvement of homozygous frame shift, missense, nonsense and single nucleotide substitution, deletion and insertion mutations in ECM1 gene LP which is located on chromosome 1q21.2 (Salih et al, 2011;Samdani et al, 2010;Kumar et al, 2009;Nasir et al, 2009). About 300 cases of LP have been so far reported.…”
Section: Discussionmentioning
confidence: 99%
“…In patient 2, at the same location of exon 8, polymorphism of nucleotide G to A (G/A) was observed ( Figure 6), but this does not cause any change in the coded amino acid. Earlier, a case of homozygous 62-bp insertion (Nasir et al, 2009) and a case of homozygous frame shift mutation leading to premature termination of ECM1 protein causing LP (Samdani et al, 2010) have been reported in Pakistani families.…”
Section: Discussionmentioning
confidence: 99%